Long-term treatment with sulfhydryl angiotensin-converting enzyme inhibition reduces carotid intima-media thickening and improves the nitric oxide/oxidative stress pathways in newly diagnosed patients with mild to moderate primary hypertension - C. Napoli; G. Bruzzese; L. J. Ignarro; E. Crimi; F. de Nigris; S. Williams-Ignarro; S. Libardi; L. Sommese; C. Fiorito; F. P. Mancini; F. Cacciatore; A. Liguori (Кардиоваскулярная терапия и профилактика)
Aim. Sulfhydryl angiotensin-converting enzyme (ACE) inhibitors exert antiatherosclerotic effects in preclinical models and antioxidant effects in patients. However, whether ACE inhibitors have any clinically significant antiatherogenic effects remains still debated. Objectives. In mildly hypertensive patients, we evaluated the effect of the sulfhydryl ACE inhibitor zofenopril in comparison with the carboxylic ACE inhibitor enalapril on carotid atherosclerosis (intima-media thickness [IMT] and vascular lumen diameter) and systemic oxidative stress (nitrite/nitrate, asymmetrical dimethyl-L-arginine, and isoprostanes). Material and methods. In 2001, we started a small prospective randomized clinical trial on 48 newly diagnosed mildly hypertensive patients with no additional risk factors for atherosclerosis (eg, hyperlipidemia, smoke habit, familiar history of atherosclerosisrelated diseases or diabetes). Patients were randomly assigned either to the enalapril (20 mg/d, n = 24) or the zofenopril group (30 mg/d, n = 24); the planned duration of the trial was 5 years. Carotid IMT and vascular lumen diameter were determined by ultrasonography for all patients at baseline and at 1, 3, and 5 years. Furthermore, nitrite/nitrate, asymmetrical dimethyl-L-arginine, and isoprostane levels were measured. Results. In our conditions, IMT of the right and left common carotid arteries was similar at baseline in both groups (P = NS). Intima-media thickness measurements until 5 years revealed a significant reduction in the zofenopril group but not in the enalapril group (P b .05 vs enalapril-treated group). This effect was coupled with a favorable nitric oxide/oxidative stress profile in the zofenopril group. Conclusion. Long-term treatment with the sulfhydryl ACE inhibitor zofenopril besides its blood pressure–lowering effects may slow the progression of IMT of the carotid artery in newly diagnosed mildly hypertensive patients. (Am Heart J 2008;156:1154.e1-1154.e8.)